2021
DOI: 10.51253/pafmj.v6i6.5647
|View full text |Cite
|
Sign up to set email alerts
|

Role of Alpha Blocker in Ureterorenoscopy.

Abstract: Objective: To determine the efficacy of alpha blockers in successful management of lower and mid ureteral stones by ureterorenoscopy. Study Design: Comparative prospective study. Place and Duration of Study: Department of Urology, Combined Military Hospital Quetta Pakistan, from Jul 2018 to Dec 2019. Methodology: Total of 150 patients having mid and lower ureteric calculi requiring ureterorenoscopy were divided into two groups. Group A included patients without pre-treatment with alpha blocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The systematic review identified 15 RCTs [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] with 1653 patients (844 alpha-blockers; 809 controls) included in the meta-analysis (Figure S1). Preoperative alpha-blocker therapy involved tamsulosin S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic review identified 15 RCTs [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] with 1653 patients (844 alpha-blockers; 809 controls) included in the meta-analysis (Figure S1). Preoperative alpha-blocker therapy involved tamsulosin S2).…”
Section: Resultsmentioning
confidence: 99%
“…The systematic review identified 15 RCTs 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 with 1653 patients (844 alpha‐blockers; 809 controls) included in the meta‐analysis (Figure S1 ). Preoperative alpha‐blocker therapy involved tamsulosin (11 studies) or silodosin (four studies) administered over 1 to 56 days before URS (median 7 days).…”
Section: Resultsmentioning
confidence: 99%